Production process for stem cell based therapeutic implants: expansion of the production cell line and cultivation of encapsulated cells - Weber, C.; Pohl, S.; Poertner, R.; Pino-Grace, P.; Freimark, D.; Wallrapp, C.; Geigle, P.; Czermak, Peter (My University, 2011)
Cell based therapy promises the treatment of many diseases like diabetes mellitus, Parkinson disease or stroke. Microencapsulation of the cells protects them against host-vs-graft reactions and thus enables the usage of allogenic cell lines for the manufacturing of cell therapeutic implants. The production process of such implants consists mainly of the three steps expansion of the cells, encapsulation of the cells, and cultivation of the encapsulated cells in order to increase their vitality and thus quality. This chapter deals with the development of fixed-bed bioreactorbased cultivation procedures used in the first and third step of production. The bioreactor system for the expansion of the stem cell line (hMSC-TERT) is based on non-porous glass spheres, which support cell growth and harvesting with high yield and vitality. The cultivation process for the spherical cell based implants leads to an increase of vitality and additionally enables the application of a medium-based differentiation protocol.
Keywords: Cell therapy; Encapsulation; Fixed bed bioreactor; Glass carrier; Mesenchymal stem cells